Integration of evidence based medicine into the clinical years of a medical curriculum - Mazen Ferwana; Ibrahim Al Alwan; Mohamed A Moamary; Mohi E Magzoub; Hani M Tamim (Wolters Kluwer Medknow Publications, 2012)
Teaching Evidence Based Medicine (EBM) helps medical students to develop their decision making skills based on current best evidence, especially when it is taught in a clinical context. Few medical schools integrate Evidence Based Medicine into undergraduate curriculum, and those who do so, do it at the academic years only as a standalone (classroom) teaching but not at the clinical years. The College of Medicine at King Saud bin Abdulaziz University for Health Sciences was established in January 2004. The college adopted a four-year Problem Based Learning web-based curriculum. The objective of this paper is to present our experience in the integration of the EBM in the clinical phase of the medical curriculum. We teach EBM in 3 steps: first step is teaching EBM concepts and principles, second is teaching the appraisal and search skills, and the last step is teaching it in clinical rotations. Teaching EBM at clinical years consists of 4 student-centered tutorials. In conclusion, EBM may be taught in a systematic, patient centered approach at clinical rounds. This paper could serve as a model of Evidence Based Medicine integration into the clinical phase of a medical curriculum.